Collaborative action research as a reflective tool for pre-service EFL teachers' inclusion. Issue 6 (2nd November 2022) - Arefian, Mohammad Hossein
ABSTRACT: Pre-service teachers face numerous challenges as beginner teachers at schools during their first practices. Therefore, teachers must reflect on their practices to solve problems and develop professionally. There are several ways to reflect on practices. Collaborative action research (CAR), as a mode of inquiry, is a method of inquiry to explore its effects on pre-service teachers' inclusion and engagement. Thus, this study aims to investigate CAR's benefits in enhancing reflections, inclusions, and engagement of pre-service teachers. In this study, 15 Iranian pre-service English language teachers' perceptions of CAR were qualitatively explored through semi-structured interviews, reflective journals, and observations to know the effect of CAR in developing reflection and inclusion. The thematic analysis of the findings found numerous advantages for pre-service teachers' personal, professional, and social development. Through CAR, pre-service teachers gain more confidence, become independent, reflect individually and socially, think and act flexibly, receive help and support, observe and predict events, and search for novel approaches and changes. This study will inform pre-service teachers, teachers, and teacher educators to utilize this form of professional development in their practices.